(untitled) (Muitas Vozes, 2013)
Foreign language teachers have traditionally been trained to think of themselves as teaching one L2 to speakers of one L1. With the advent of globalization and the increased mobility of humans, goods and capital, the multilingual and multicultural nature of national societies has become both more prevalent and more visible. Language classrooms are populated nowadays with students who don’t necessarily speak a common national language and who speak a variety of second, immigrant or heritage languages. They are multilingual not only in the strict sense of being equally fluent in more than one linguistic code, but also in the sense that they have different outlooks, different upbringings, they have been socialized in different ways. They have less and less of a consensus on what is an appropriate, polite behavior, nor even what is expected in school.